Rivers of gold [large type] - Peterson, Tracie (Peterson, Tracie. Yukon quest, 2016)
Alaska in the late 1800s: Miranda Colton, presumed dead, finds herself under the care of a native Alaskan and a studious botanist from England, Teddy Davenport. Miranda only longs to find her friends and continue north. She fears that her chances are diminishing with each passing day. Teddy is deeply committed to his research of the unique landscape of the rugged Alaskan frontier. But despite his intentions, Miranda's presence awakens a deep tenderness in his character. As a friendship with Teddy blossoms, Miranda struggles inwardly with her earlier dreams. Then the menacing force from the past threatens to destroy everything she holds dear.